ANALYSIS OF QUALITY CONTROL OF T-SHIRT SCREEN PRINTING PRODUCTS WITH SIX SIGMA DMAIC METHOD ON CV. MACCA CLOTHING. - Nurhayati Rauf; Ahmad Padhil; Takdir Alisyahbana; Anis Saleh; Muhammad dahlan; Rahmaniah Malik; Andi Pawennari; Nurul Chairany (Center for Study and Journal Management FTI UMI, 2022)
CV. Macca Clothing is a company engaged in Clothing screen printing. The resulting product is a short sleeve t-shirt screen printing. In producing the production, on average per month there are defective products of 6% types of defects, namely blurred colors, wrong colors, and wrong screen printing. Therefore, this study aims to providelevels sigma and DPMOand then analyze the factors causing disability and provide suggestions for improvements to reduce defective products at CVMacca Clothing. The data collection method used is to conduct interviews with CV.Macca Clothing. Then in analyzing the data using the method DMAIC and theapproach six sigma.From the research results, thevalue DPMO is 21,000 and the conversion result is 3.53, which means that out of a million opportunities there will be 3.53 possibilities for the production process to produce defective products. in thelevel stage sigma CV.Macca Clothing has not yet reached thelevel Six Sigma, but it is still in the average industrial condition because in the production process there are still product defects that have not reached zero defect. The factors that cause defects in the product are the operator is not careful in doing the work, the quality of raw materials is not good, the cleanliness of the equipment is not maintained, and the production room facilities are inadequate. From the results of the analysis based on the implementation tools kaizen , the control and improvement to reduce defects that must be carried out by CV.Macca Clothing is to carry out stricter supervision or control, carry out regular machine maintenance, and provide complete facilities.